The impact of individual differences on investigative interviewing performance: a test of the police interviewing competencies inventory and the five factor model. (15th January 2021) - Akca, Davut; Eastwood, Joseph
ABSTRACT: We examined whether and how individual differences impact investigative interviewing performance by using the Police Interviewing Competencies Inventory (PICI) and the Five Factor Model (FFM) in a two-step research design. In Study 1, the structure of a modified version of the PICI was assessed using a general population sample (N = 300) and a four-dimensional aptitudes scale was created. In Study 2, student participants (N = 154) completed the aptitudes and the FFM scales, and then interviewed witnesses who watched a mock robbery crime video. Interviewer performance was assessed based on the amount of details they could elicit, the perception of the witness, and researcher ratings of behaviours and question usage. Three dimensions of the FFM were correlated with the success measures: Agreeableness with witness perception and appropriate questioning, Extraversion with researcher ratings and inappropriate questioning, and Openness with researcher ratings. Only the Communicative-Insisting dimension of the aptitudes scale predicted high researcher ratings. Findings might help police departments to identify potential successful interviewers.